First record of glass eye, Heteropriacanthus cruentatus (Lacepede, 1801) (Cookeolus boops Schneider, 1801) from Indian waters - Nayak, T Harish; Abdurahman, K P; Zacharia, P U; Mohamed, K S (Indian Journal of Fisheries, 2011)
The first record of occurrence in India of a relatively unfamiliar species of marine fish belonging to the family Priacanthidae is presented here. A single specimen obtained from trawl catch at Mangalore was identified as the glass eye, Heteropriacanthus cruentatus (Lacepede, 1801). The name Cookeolus boops (Schneider, 1801) is now used as the junior synonym. The identifying morphometric and meristic characters, location and depth of capture of the species are given.